Indonesia’s Foreign currency reserves: An Analysis of the Influencing Factors - Jusmer Sihotang; Martin Luter Purba; Nancy Nopeline; Meli Sukawati Ujung (PT FORMOSA CENDEKIA GLOBAL, 2023)
The impact of exports, inflation, the rupiah exchange rate (ER), and foreign direct investment (FDI) on Indonesia's foreign currency reserves is examined in this study (FER). The FER is the dependent variable in the study model's multiple linear regression equations, which also include the independent variables exports, inflation, the exchange rate of the rupiah, and foreign direct investment in Indonesia. The data used is from 2001 to 2021, and the model estimation technique is Ordinary Least Squares. The study demonstrates that FER is highly impacted by exports, inflation, the exchange rate of the rupiah, and FDI in Indonesia. FER is significantly and favorably impacted by exports and FDI. FER is negatively and significantly impacted by inflation in Indonesia. The rupiah ER does, however, have a slight and favorable impact on FER.